Relationship Between Dermatoglyphic Pattern and Dental Caries Among Pre-School Children of Kathmandu, Nepal (Journal of Nobel Medical College, 2025)
Background: Development of dermal ridges and primary palate occurs at same time of intrauterine life. Also, epithelium of both enamel and finger buds have ectodermal origin due to which dermatoglyphics is considered as a genetic marker of dental caries. Therefore, this study was conducted to determine relationship between dermatoglyphic pattern and dental caries status among preschool children in Kathmandu, Nepal.Materials and Methods: An analytical cross-sectional study was conducted among 236 schoolchildren of 2-6 years (Group 1, dmft=0, Group 2, dmft≥1). Dermatoglyphic pattern was assessed from all 10 fingers of two hands using inkpad and fingerprint cards and dmft index was recorded. Data collected were analyzed in statistical package for social sciences version 24. Mean, standard deviation, frequency and percentage were calculated for descriptive analysis. Chi-square test and Mann Whitney-U test were done to determine the relationship between dermatoglyphic pattern and caries experience.Results: Arch pattern in left thumb was significantly associated with caries free children (p=0.023).  Caries-free group had significantly higher counts of arches (p=0.007), while whorl patterns were prevalent in children with dmft≥1 (p=0.017) in right hand. Significantly more loops in caries-free group (p=0.030) were found in left hand. Overall observations showed significantly higher number of whorl patterns in children with dmft≥1 (p=0.017).Conclusion: The findings of this study showed a potential relationship between dermatoglyphic patterns and dental caries experience in preschool children. Children with caries experience had a significantly higher number of whorl patterns whereas arch and loop patterns were more prevalent in caries-free children.